2008
DOI: 10.1038/nprot.2008.141
|View full text |Cite
|
Sign up to set email alerts
|

A simple and reproducible 96-well plate-based method for the formation of fungal biofilms and its application to antifungal susceptibility testing

Abstract: The incidence of fungal infections has increased significantly over the past decades. Very often these infections are associated with biofilm formation on implanted biomaterials and/or host surfaces. This has important clinical implications since fungal biofilms display properties that are dramatically different from planktonic (free-living) populations, including increased resistance to antifungal agents. Here we describe a rapid and highly reproducible 96 well microtiter-based method for the formation of fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
278
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 731 publications
(285 citation statements)
references
References 30 publications
(30 reference statements)
2
278
0
5
Order By: Relevance
“…The tetrazolium salt XTT (2,3-bis[2-methoxy-4-nitro-5-sulfophenyl]-2H-tetrazolium-5-carboxanilide inner salt) (Sigma, St. Louis, MO) was used to measure the metabolic activity of A. fumigatus. Whereas XTT is a direct measure of the metabolic activity of cells, previous studies of A. fumigatus have indicated that XTT results are linear with mass and equated the XTT result with dry weight (19)(20)(21). Our confocal microscopy studies also address this point.…”
Section: Iron Chelators and Feclsupporting
confidence: 52%
See 1 more Smart Citation
“…The tetrazolium salt XTT (2,3-bis[2-methoxy-4-nitro-5-sulfophenyl]-2H-tetrazolium-5-carboxanilide inner salt) (Sigma, St. Louis, MO) was used to measure the metabolic activity of A. fumigatus. Whereas XTT is a direct measure of the metabolic activity of cells, previous studies of A. fumigatus have indicated that XTT results are linear with mass and equated the XTT result with dry weight (19)(20)(21). Our confocal microscopy studies also address this point.…”
Section: Iron Chelators and Feclsupporting
confidence: 52%
“…The 96-well assay is both sparing of reagents and allows more replicates to be studied concurrently, which increases the chances of statistical significance occurring when differences between groups are small, e.g., at the inflection point of a dose-response curve. An analogous 96-well assay used to assay antifungal drugs, and differing in specifics from ours, was previously described (19). The interpretations made here are based on 7 experiments on biofilm formation in the 12-well format and 9 in the 96-well format, which included 10AF as a reference control.…”
Section: Iron Chelators and Feclmentioning
confidence: 99%
“…Aspects of this model were changed over time by other research groups. The plastic bottoms of the wells of multiwell tissue culture dishes, rather than serum-treated catheter discs, were employed as substrata for purposes of expediency, since tissue culture plastic proved to be adhesive (180)(181)(182). YNB medium was also replaced with different media to support planktonic growth and biofilm formation (38).…”
Section: The Douglas Model: a Good Starting Pointmentioning
confidence: 99%
“…For detection of EE on mature biofilms, biofilms pregrown for 24 h were treated with different concentrations of EE and were incubated for 24 h at 37°C. After incubation, the supernatant was discarded and XTT (Sigma, USA) was added to the prewashed biofilms (69). The plate was incubated in the dark for 2 to 3 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%